PENGARUH PROBLEM BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMA NEGERI JUMAPOLO TAHUN PELAJARAN 2013/2014. - Andi Wahyudi; Marjono Marjono; Harlita Harlita (Universitas Sebelas Maret, 2015)
The research aims to examine the influence of Problem Based Learning model on science process skills and biology learning achievement. This research held upon senior high school student of SMA Negeri Jumapolo in academic year 2013/2014. This research was a quasi-experimental. This research design used was posttest Only Control Group Design with the experiment grup applying Problem Based Learning model and control group applying conventional learning model. The population of research was all X graders of SMA Negeri Jumapolo in academic year 2013/2014. The technique sampling used was Cluster Sampling. The sample of research consisted of X.2 grade as the experiment group and X.3 grade as control group. Techniques of data collecting using tests, observation and documentation. Documentation was using skor of the 2nd half of the school year test in academic year 2013/2014. Essay test to measure learning outcomes of knowledge. Observation sheet for measure of science process skills and attitude domains of learning outcomes. The hypothesis testing using Manova test with SPSS version 16. This research concluded that the Problem Based Learning affected significantly the science process skills (Sig. 0,001 < 0,05) and the biology learning achievement in knowledge domains (Sig. 0,008 < 0,05) but has no affected significantly on biology learning achievement in attitude domains (Sig. 0,615 > 0,05) of the X graders SMA Negeri Jumapolo in academic years 2013/2014. Keywords: Problem Based Learning, Science Process Skills, Learning Outcomes in Biology